The Development of Physical Parameters and E-Report Physical Condition Software For U-15 Badminton Athletes (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The identification for talented athletes in Djarum Badminton Club audition is necessarily needed to measure physical test parameters for under 15 years old players. Therefore, it could be expected to have the potential talents. This research aims to produce physical parameters test for U-15 badminton athletes. Samples of this research are Djarum Badminton Club athletes of under 15 years old. Research method uses research and development (R n D) approach with analysis descriptive percentage technique. The results : the assessment from the expert with average score 4,59 (very good). Validity : 1) sit up : 91,7 (very high) 2), push up : 83,3 (very high), 3) balke: 75 % (high), 4) sit and reach : 91,7 (very high), 5) sprint 20 m : 75 % (high), 6) grip strength test : 75 % (very high), 7) court agility test : 100 % (very high), 8) vertical jump test : 100% (very high) and 3 steps medicine ball throw test : 91,7 % (very high). Reliability: 0,917. Conclusions: validity of 7 test items is very high category and the 2 test items is high category, meanwhile the reliability is very high. So this parameters can be used in Djarum Badminton Club auditions for U-15s.